The Actualization of Adiwiyata School Values Through the Environmental Campaign of Al-Fattah Islamic Junior High School, Semarang - Naryatmojo, Deby Luriawati; Kusumantoro, Kusumantoro; Sholeh, Muh; Simbolon, Andri Sumihar (Jurnal Abdimas, 2024)
Tambakrejo Village faces complex environmental issues, such as waste accumulation and flooding. This is exacerbated by the low awareness among the community regarding waste management and environmental preservation. To address these challenges, the Environmental Education Movement in Schools was initiated as an implementation of school-based environmental education. The program aims to encourage and develop environmentally conscious and culturally aware schools that are capable of participating in and implementing efforts to preserve the environment within the framework of sustainable development. The PBLHS (Environmental Education Movement) at SMP Al-Fattah, Tambakrejo Village, Semarang City, is supported by Saka Energi Muriah Limited and Semarang State University, and includes the following activities: (1) socialization, (2) preparation of the Learning Program Plan (RPP), (3) training of Adiwiyata cadres, (4) integration of PBLHS into the curriculum, (5) implementation of PBLHS, (6) provision of facilities and infrastructure, and (7) monitoring and evaluation. The results of the activities show an increase in students' awareness of waste and energy management, as well as the development of environmentally friendly habits at the school through intracurricular, co-curricular, and extracurricular activities. The development of facilities such as waste sorting stations, environmental posters, and the formation of Adiwiyata cadres strengthens the role of students as agents of change within the school and the surrounding community. The implementation of PBLHS at SMP Al-Fattah has successfully instilled environmental preservation values in students and fostered environmentally conscious character.